Analysis of different height systems along the Sava river - Koler, Božo; Jakljič, Samo; Breznikar, Aleš (Geodesy and Cartography, 2012)
The paper presents a project of renovating a levelling line from Hydroelectric Power Plant Medvode to Hydroelectric Power Plant Vrhovo. The levelling line is situated along the Sava River. A new height of benchmark was needed as a vertical reference system for the project building up a new HPP between the previously mentioned HPP. Further, the paper presents processing data on measurements (scale and temperature corrections). Gravimetric measurement was performed due to the determination of the geopotencial number and dynamic and normal heights. Slovenian official vertical system contains normal orthometric heights so we also calculated normal orthometric heights. Moreover, the article discusses the accuracy of measurements (levelling and gravimetric) and analyses height calculated in different vertical systems and vertical movements along the levelling line. Įvairių aukščių sistemų prie sava upės analizė Santrauka. Pateikiamos niveliavimo renovacijos projektas nuo Medvode iki Vrhovo hidroelektrinių. Niveliaciniai ėjimai projektuojami išilgai Savos upės. Nauja niveliavimo markių sistema tarnaus kaip referencinis vertikalus tinklas tarp minėtų hidroelektrinių. Toliau numatomas matavimo duomenų apdorojimas (mastelio ir temperatūros pataisos). Numatomi gravimetriniai matavimai, reikalingi nustatant geopotencialą ir dinaminius bei normalinius aukščius. Slovėnijoje naudojama normalinė ortometrinė aukščių sistema, todėl mes skaičiuojame normalinius ortometrinius aukščius. Pateikiami matavimų tikslumo skaičiavimai (niveliavimo ir gravimetriniai), apskaičiuotų aukščių analizė skirtingose aukščių sistemose ir niveliavimo ėjimo vertikalūs judesiai. First published online: 03 Aug 2012